Addressing the What and How of Online Services: Positioning Supporting-Services Functionality and Service Quality for Business-to-Consumer Success - Cenfetelli, Ronald T.; Benbasat, Izak; Al-Natour, Sameh (Information Systems Research, 2008)
With the continued growth of business-to-consumer (B2C) e-business, online vendors are providing an increasing array of services that support and enhance their core products or services. For example, Amazon.com does not just sell books; it also enhances that core product with automated product recommendations, “wish list” tracking, order status updates, customer reviews, and many other valuable supporting services. These supporting services are made possible exclusively through the design and deployment of information technology (IT) to provide website supporting services functionality (SSF). In this paper, we define and develop the concept of B2C SSF and investigate how IT can support core products or services. We theorize the role that SSF plays in an environment where individuals who visit B2C websites are not only customers but also technology users. Given the unique online environment that amalgamates vendor services with information systems (IS), our model integrates theories from both services marketing and technology acceptance to help explain the behavior of these customers/users. In doing so, we investigate the role of the extensively researched concept of service quality in relation to SSF. Although service quality provides guidance for how supporting services should be provided (e.g., responsively and reliably), it does not address what those services are (e.g., product recommendations). SSF addresses this deficiency, thus providing both theoretical and practical benefits through a focus on IT design and deployment. The results of a field study support that SSF is an important predictor of customer beliefs and behavior, beyond that predicted by service quality alone. SSF is an important concept to consider—theoretically and practically—in IT-mediated B2C service.